A method for converting microdosimetric spectra in diamond to tissue in proton therapy. Issue 7 (18th April 2022) - Yu, Songke; Fan, Wenjie; Tang, Lin; Liao, Xianli; Liu, Ze
Abstract: Purpose: Diamond has been regarded as a promising microdosimeter in radiation protection and radiotherapy due to its excellent properties. However, as the diamond is not tissue equivalent, a conversion of the measured spectra in the diamond microdosimeter to the tissue site is needed. In this work, we intend to deduce a method for converting the microdosimetric spectra from diamond to tissue in the proton therapy application based on the Chapman–Kolmogorov equation and investigate the validity of this method in spectral conversion. Methods: The comparison of stopping power and energy deposition distribution of diamond and tissue shows that the conversion of the spectra in diamond to tissue can be performed by a simple scaling factor. Therefore, the equivalence of the energy deposition spectra in the diamond microdosimeter and a tissue site of the same size in the same radiation field was studied first to obtain the scaling factor. Then, the spectra conversion method was derived from the Chapman–Kolmogorov equation and the scaling factor. The Geant4 simulation was employed to settle this study. Results: Theoretical and Geant4 simulation results indicate that the linear stopping power ratio of diamond to tissue is adequate to convert the microdosimetric spectra in diamond to tissue of identical dimension. The conversion results indicate that the energy deposition spectra converted from diamond to bone agree well with the spectra calculated by Geant4 along the Bragg curve. As for water, a good agreement of the converted and calculated spectra was found at the plateau of the Bragg curve and the distal part of the Bragg peak. At the proximal part of the Bragg peak, the converted and calculated spectrum is poorly coincident. Conclusions: The method of the energy deposition spectra conversion from the diamond microdosimeter to the tissue site of equal size shows relatively good results in most situations. But the deficiency was also found. Therefore, further investigation is needed to improve the reliability of this method.